Plasma ammonia synthesis over mesoporous silica SBA-15. (23rd April 2021) - Gorky, Fnu; Guthrie, Shelby R; Smoljan, Courtney S; Crawford, James M; Carreon, Moises A; Carreon, Maria L
Abstract: Herein we demonstrate the synthesis of ammonia via atmospheric dielectric barrier discharge plasma discharge over silica. We evaluated the performance of three structural different silicas: non-porous silica, fumed-silica and mesoporous SBA-15 silica. The mesoporous SBA-15 sample resulted in an ammonia synthesis rate per gram of catalyst at least three times higher than that of the non-porous and fumed silica when employing a hydrogen rich gas feed. The hierarchical ordered pore size in the mesoporous range of SBA-15 allowed us to observe experimentally, the pore size effect in the plasma discharge. Specifically, the ammonia production is enhanced by the presence of mesopores that can effectively enable the discharge diffusion into the pore as predicted by theoretical calculations. The importance of the porous structure was confirmed by optical emission spectra which indicates a similarity on the relative intensity on the main plasma activated species in the gas phase such as N2 +, NH and H α for the three silicas employed in this work i.e. non-porous, fumed and mesoporous (SBA-15). However, the remarkable ammonia production when employing the SBA-15 shows that despite the similarities in the gas phase the main differences might be attributed to the diffusion of the plasma discharge into the pores.